Problem-based case study to enhance critical thinking in student nurses - Mogale, N M; Botes, A C (Curationis (Pretoria), 2001)
The use of traditional teaching methods, for example the lecture method, does not stimulate critical thinking in student nurses. This problem can be solved by the utilisation of problem-based case study in the classroom/clinical setting. The purpose of this study is to describe guidelines for the implementation of problem-based case study in a clinical setting among first year, comprehensive course students at the Northern Province College of Nursing: Sovenga campus. The research design of this study was qualitative, explorative, descriptive and contextual and was conducted in the following phases: Phase 1: The development and implementation of a program for problem-based case study in the clinical setting; Phase II: The experiences of student nurses who were exposed to problem-based case study in the clinical setting; Phase III: The perceptions of tutors regarding the implementation of problem-based case study in the clinical setting (focus group), and; ase IV: Guidelines for the implementation of problem-based case study. The data from Phases I, II and III were used to formulate guidelines for the implementation of problem-based case study. The sample group consisted of all 69 first year student nurses at the Northern Province College of Nursing: Sovenga campus and ten tutors teaching clinical courses at the same campus. The Tesch (1990) approach is used for data analysis. Nine guidelines for the implementation of a problem-based case study approach were formulated and recommendations for development of an instrument to measure critical thinking in nursing were recommended.